A Pronounced Halogen Effect on the Organogelation Properties of Peripherally Halogen Functionalized Poly(benzyl ether) Dendrons. Issue 14 (24th February 2016) - Feng, Yu; Chen, Hui; Liu, Zhi‐Xiong; He, Yan‐Mei; Fan, Qing‐Hua
Abstract: An interesting halogen‐substituent effect on the organogelation properties of poly(benzyl ether) dendrons is reported. A new class of poly(benzyl ether) dendrons with halo substituents decorating their periphery was synthesized and fully characterized. A systematic study on the gelation abilities, thermotropic behaviors, aggregated microstructures, and mechanical properties of self‐assembled organogels was performed to elucidate the halogen‐substituent effects on their organogelation propensity. It was found that the exact halogen substitutions on the periphery of dendrons exert a profound effect on the organogelation propensity, and dendrons G n ‐Cl ( n =2, 3) and G2 ‐I proved to be highly efficient organogelators. The cooperation of multiple π–π, dispersive halogen, CH–π, and weak C−H⋅⋅⋅ X hydrogen‐bonding interactions were found to be the key contributor to forming the self‐assembled gels. Dendritic organogels formed from G n ‐Cl ( n =2, 3) in 1, 2‐dichloroethane exhibited thixotropic‐responsive properties, and such thixotropic organogels are promising materials for future research and applications. Abstract : Halogen‐assisted dendritic organogels : A new class of poly(benzyl ether) dendrons with halo substituents decorating their periphery (see figure) was synthesized and fully characterized. They exhibited pronounced halogen‐substituent effects on their organogelation properties.